The bond as a soft technology in the daily routine of the Family Health Strategy: perception of the user - Bianca Pozza dos Santos; Fernanda Nizoli Nunes; Patrícia Tuerlinckx Noguez; Adriana Roese
Objective.This study aimed to analyze the production of a bond between users and health care professionals in a Family Health Unit (FHU). Methods. This was a qualitative, descriptive study, with 33 hypertensive and/or diabetic users. Interviews were transcribed, analyzed and data were compared to the literature. Results. The users who have been accessing the FHU for years stated that the bond with professionals has grown weak, it is a fragile bond. When it does exist, it is directed toward some professionals in the team. A disruption in the bond was also mentioned in some situations, owing to individual issues. Establishment of a bond between the user and the health care professionals in the reference FHU consists of a soft technology. Therefore, it impacts quality of health care and the prevention and management of chronic diseases. Conclusion. Establishment of a bond is essential for health care professionals to become references for the users of health care services.